Democratic Innovations Help Fight Covid-19 in Latin America - Thamy Pogrebinschi (WZB Berlin Social Science Center, 2020)
While some Latin American countries remain in the middle of the pandemic and their governments have been either unable or unwilling to do anything about it, civil society has begun to initiate a considerable number of digital democratic innovations.
Keywords: 300; Latin America; epidemic; contagious disease; Coronavirus; COVID-19; political stability; social inequality; coping; citizens' involvement; civil society; crowdsourcing; digitalization; social intelligence; democracy; innovation